SUKARNO'S THINKING CONTRIBUTION IN THE FLOW INDONESIAN EDUCATION, 1945-1967 - Cici Fanisa Yulia Dwi Jayanti; Sahru Romadloni; I Kadek Yudiana; Mahfud (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The purpose of this study is to analyze President Sukarno's educational thoughts and policies which have an impact on the development of education in Indonesia. The method used in this study is the Historical Method with four steps, namely Heuristics, Criticism, Interpretation, and Historiography. The results of the research show that before Indonesia's independence, education had begun to develop with the existence of different types of schools. After Indonesia's independence, the education system was revitalized and changed in accordance with the ideals of an independent Indonesian nation. Sukarno's thoughts and policies on education had a major impact on the development of education in Indonesia. Manipol-Usdek emphasizes equality of access and participation in education for all levels of society, while Trisakti emphasizes the importance of empowering the younger generation through education to build the intellectual and moral strength needed in nation building. The results of this study indicate that Sukarno's thoughts and policies on education have had a positive influence on education in Indonesia.